Mineirinho em cena: uma releitura teatral contemporânea biopolítica da crônica de Clarice Lispector - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2026)
This work consists of an analysis and theatrical adaptation of Clarice Lispector's chronicle Mineirinho, seeking to contribute to artistic productions that combine literature and theater as instruments of social reflection. The research investigates the meanings and interpretative layers of the original text, relating them to the contemporary context and the permanence of issues such as violence, injustice, and inequality. The study is grounded in concepts such as necropolitics and biopolitics, discussing how power decides on the life and death of certain bodies and how these structures are perpetuated in Brazil today. The proposal culminates in the creation of a monologue that engages directly with the audience, even those unfamiliar with the work, encouraging sensitive and critical listening. The interest in this research arose from a personal, academic, and artistic trajectory, marked by experiences with theater and cultural projects focused on memory and identity, which led to an understanding of the stage as a space for resistance and dialogue. The adaptation begins with an ethical and political perspective on Clarice Lispector's work, seeking to redefine its power in the contemporary scene.
Keywords: Clarice Lispector; Mineirinho; Monólogo; Adaptação Teatral; Necropolítica; Biopolítica; CNPQ::LINGUISTICA, LETRAS E ARTES::ARTES::TEATRO; ODS 4 – Educação de qualidade; ODS 10 – Redução das desigualdades; ODS 16 – Paz, justiça e instituições eficazes